Formulation Research and Antibacterial Activity Test of Face Mist Preparation from Ethanol Extract of Papaya Leaves (Carica Papaya L.) Against Propionibacterium Acnes - Mustaanah, Aulia Nur; Fadel, Muhammad Nurul; Khudzaifi, Muhamad (Advances in Healthcare Research, 2025)
Purpose: The purpose of this study was to formulate a face mist preparation containing ethanol extract of papaya leaves (Carica papaya L.) at concentrations of 10%, 15%, and 20%, and to evaluate its antibacterial activity against Propionibacterium acnes, a primary acne-causing bacterium. Research Method: This study employed a laboratory-based experimental design with a post-test-only control group. Data were collected through experimental observations. The face mist was formulated with three extract concentrations (F1: 10%, F2: 15%, and F3: 20%), with a face mist base as the negative control and clindamycin as the positive control. The preparations underwent organoleptic, pH, homogeneity, and spreadability tests. Antibacterial activity was evaluated using the disc diffusion method, and the data were analyzed using One-Way ANOVA with a significance level of p < 0.005. Results and Discussion: The formulations met the physical property standards, showing a brownish-green color, liquid consistency, and a characteristic papaya leaf aroma. All samples were homogeneous, with pH values ranging from 5.08 to 5.16, and spreadability between 5.33 and 5.75 cm. The highest antibacterial activity was observed in F3 (20%) with an average inhibition zone of 16.3 mm. Implications: The findings suggest that papaya leaf ethanol extract is a promising natural ingredient for face mist formulations with antibacterial properties, offering potential as an alternative acne treatment product.